3
$\begingroup$

This is a question about Fibonacci sequences, a sequence in which the previous terms build up upon the current term (e.g. $F_1 + F_2 = F_3$ where $F_1 = F_2 = 1$). How would I go about proving $F^2_{n+1} - F_nF_{n+2} = (-1)^n$?

$\endgroup$
  • $\begingroup$ Induction......? $\endgroup$ – Permian Jan 19 '15 at 16:53
  • $\begingroup$ Very detailed comment, @1234. Would you care to elaborate, please? $\endgroup$ – Don Larynx Jan 19 '15 at 16:53
1
$\begingroup$

$n=1$.

$$F^2_{2}-F_1F_3=1-1.2=-1=(-1)^1$$ Correct

Suppose true for $n$, so we assume that $F^2_{n+1} - F_nF_{n+2} = (-1)^n$ So for case $n+1$

$$ F^2_{n+2} - F_{n+1}F_{n+3} =(-1)(F^2_{n+1} - F_{n}F_{n+2})=(-1)(-1)^n=(-1)^{n+1}$$

$\endgroup$
2
$\begingroup$

Hint: Prove that $$F^2_{n+1} - F_nF_{n+2} = -(F^2_{n} - F_{n-1}F_{n+1})$$

and the result follows immediately by induction.

$\endgroup$
2
$\begingroup$

I think I can without this by induction

Note $$F_{n+1}F_{n}=(F_{n+2}-F_{n})F_{n}=F_{n+2}F_{n}-F^2_{n}\tag{1}$$ and by other hand we also $$F_{n}F_{n+1}=(F_{n+1}-F_{n-1})F_{n+1}=F^2_{n+1}-F_{n+1}F_{n-1}\tag{2}$$ with $(1)=(2)$ so $$F^2_{n+1}-F_{n}F_{n+2}=-(F^2_{n}-F_{n+1}F_{n-1})$$ so $\{F^2_{n+1}-F_{n}F_{n+2}\}$ is Geometric progression $$F^2_{n+1}-F_{n}F_{n+2}=(-1)^{n-1}[F^2_{2}-F_{1}F_{3}]=(-1)^n$$

$\endgroup$
  • $\begingroup$ That last step precisely boils down to induction ;) $\endgroup$ – AlexR Jan 19 '15 at 17:06
  • $\begingroup$ hello,use Geometric progression not use induction $\endgroup$ – math110 Jan 19 '15 at 17:22
  • $\begingroup$ The thing is the Geometric progression formula is proven using induction. You'll need to use it in one way or another :P $\endgroup$ – AlexR Jan 19 '15 at 17:24
  • $\begingroup$ AlexR is correct! $\endgroup$ – Olivier Bégassat Jan 19 '15 at 18:11
1
$\begingroup$

you can see $$\begin{bmatrix} f_{n+2} & f_{n+1}\\ f_{n+1}& f_{n} \end{bmatrix}=(\begin{bmatrix} 1 &1 \\ 1 & 0 \end{bmatrix})^{n+1}$$for example put n=1 $$\begin{bmatrix} f_{3} & f_{2}\\ f_{2}& f_{1} \end{bmatrix}=(\begin{bmatrix} 1 &1 \\ 1 & 0 \end{bmatrix})^{2}=\begin{bmatrix} 1 &1 \\ 1 & 0 \end{bmatrix}\begin{bmatrix} 1 &1 \\ 1 & 0 \end{bmatrix}=\begin{bmatrix} 2 &1 \\ 1 & 1 \end{bmatrix} $$if you put n=2 $$\begin{bmatrix} f_{4} & f_{3}\\ f_{3}& f_{2} \end{bmatrix}=(\begin{bmatrix} 1 &1 \\ 1 & 0 \end{bmatrix})^{3}=\begin{bmatrix} 2 &1 \\ 1 & 0 \end{bmatrix}\begin{bmatrix} 1 &1 \\ 1 & 0 \end{bmatrix}=\begin{bmatrix} 3 &2 \\ 2 & 1 \end{bmatrix} $$f(1)=1 ,f(2)=1 ,f(3)=2, f(4)=3 and so on ...

so now det(l.h.s)=det(R.h.s) $$det(\begin{bmatrix} f_{n+2} & f_{n+1}\\ f_{n+1}& f_{n} \end{bmatrix})=det(\begin{bmatrix} 1 &1 \\ 1 & 0 \end{bmatrix})^{n+1}) \\f_{n+2}f_{n}-f_{n+1}f_{n+1}=0-(-1)^{n+1}\\f_{n+2}f_{n}-f_{n+1}f_{n+1}=-(-1)(-1)^{n}=(-1)^{n}$$

$\endgroup$
  • $\begingroup$ How is the matrix true for $f_n = 3$? $\endgroup$ – Don Larynx Jan 19 '15 at 17:19
  • $\begingroup$ i made 2 example for it $\endgroup$ – Khosrotash Jan 19 '15 at 17:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.